Topotecan and liposomal doxorubicin in recurrent ovarian cancer: is sequence important?. (1st January 2006) - Dupont, J.; Aghajanian, C.; Andrea, G.; Lovegren, M.; Chuai, S.; Venkatraman, E.; Hensley, M.; Anderson, S.; Spriggs, D.; Sabbatini, P.
Abstract : A variety of agents have emerged to treat patients with recurrent epithelial ovarian cancer (EOC). Most patients receive both topotecan (T) and liposomal doxorubicin (D); however, there are no data regarding the benefit of a sequence—D followed by T (DT) or T followed by D (TD). We identified 89 consecutive patients with recurrent EOC, who received both D and T from January 1994 to January 2004 at Memorial Hospital. We compared the duration of treatment, toxicity, and overall survival (OS) for patients who received either DT or TD. Sixty-four patients received DT, and 25 patients received TD. The groups were balanced regarding age, stage, surgical debulking, platinum sensitivity, prior therapy, and intervening drugs between D and T. Median numbers of cycles on DT and TD were seven and six, respectively ( P = 0.61); there was no difference in duration based on platinum sensitivity. Removal from therapy for toxicity was similar, DT (22%) and TD (36%) ( P = 0.18). Finally, there was no difference in median OS based on sequence, DT (18.28 months) and TD (17.75 months) ( P = NS). Platinum sensitivity did not affect median OS based on sequence. Based on duration, toxicity, and OS there is no advantage of one sequence of D and T when treating patients with recurrent EOC.